The Role of Knowledge-Based Human Resources in Developing Personal Creativity and Increasing Productivity - Endang Meiliani; Mustika; Wenny Desty Febrian; Indra Sani; Wella Sandria (Indonesian Journal Economic Review (IJER), 2026)
Knowledge-based human resources are the embodiment of intellectual capital, which plays a central role in driving progress in the modern economic era. When individuals place knowledge as the primary foundation of their activities, they no longer rely solely on physical strength or repetitive mechanical skills, but instead optimize their cognitive capacity to digest, analyze, and reconstruct information into new ideas. This in-depth and multidimensional knowledge acts as a powerful fuel for the development of personal creativity. This study aims to explain the role of knowledge-based human resources in developing personal creativity and increasing productivity. This research method is qualitative, using secondary data such as books and journal articles. The research results show that the role of knowledge-based human resources is a crucial asset in the modern economic era. Unlike conventional human resources that rely on physical strength or routine, knowledge-based human resources rely on intellectual wealth, expertise, and analytical skills in developing personal creativity and increasing productivity.